ESTIMASI DAMPAK PROSES REDUKSI CONE CRUSHER TERHADAP FRAGMENTASI BATUAN DI CV. TAPIAN NAULI MALAU - Zebua, Ridho Duno Putra; Sebayang, Sedarta; Tambunan, Yunita K. (LPPM ISTP, 2024)
Construction aggregates are generally rocks resulting from the mining process. Rock undergoes a size reduction process using rock crushing equipment called a crusher. The process of reducing its size is carried out in stages, starting from primary crushing, additional crushing (secondary crushing) and final crushing (thertiary crushing). The final stage of crushing is usually carried out using a cone crusher because it only reduces the size without crushing (Fuerstenau et all, 2009). This research was conducted at CV. Tapian Nauli Malau, Dusun Tappe-Tappe, Simpang Bage Village, Pamatang Silimahuta District, Simalungun Regency. The formulation of the problem in this research is what are the characteristics of the output product of tertiary crushing (cone crusher), what is its circularity and aspect ratio, and what is the impact of the process on grain size. The purpose of this study was to determine the characteristics of the tertiary crushing (cone-crusher) output product, aspect ratio, circularity and the impact of the process on grain size. The method used in this research is comparative analysis. The results of the study found that the average fragment size of the output cone crusher was 3.62 cm. But in the primary 19.00 cm, secondary 8.30 cm, and input cone crusher 6.00 cm. The shape of the cone crusher output fragment is angular (1.46), with low roundness (0.60). However, the primary output is 1.48 and the secondary is 1.47. The reduction ratio of cone crusher is 1.5. However, the reduction ratio for primary crushing is 4 and for secondary crushing is 2. The impact of the process on grain size at the output of a cone crusher that relies on scouring is that it does not change the shape of the fragments, they remain angular, including the degree of roundness.